Calculation Of Minimum Shaft Bearing Diameter Of ORC Turbine-Generator 100 kW And Analysis Using Finite Element Method - Hermawan, Hana; Guardi, Arli; Purnama, Harry; Sakban, Sakban (Jurnal Polimesin, 2024)
This study aims to analyze the strength of a turbine-generator shaft and determine the minimum diameter of the shaft using the Finite Element Method (FEM). The research problem is to ensure the shaft's strength and durability, considering the high rotation speed of the hermetic turbine generator. The methodology involves using Finite Element Method and comparing the calculated minimum diameter with the physical properties of stainless steel 420. The research design includes modeling the shaft using SolidWorks and conducting FEM analysis using Ansys Mechanical Structure. The results show that the maximum von Mises stress is 50.6 MPa, which is below the material's yield strength of 345 MPa. The deformation of the shaft is minimal, and the natural frequencies indicate no critical speed below the rated RPM of the turbine-generator. The implications of this study are that the analyzed shaft design is safe and meets the strength requirements for the turbine-generator.